Military spouses' relationship with media during Operation Iraqi Freedom - Kohler, Alison (Kansas State University, 2008)
Military spouses have a complex relationship with news coverage of Operation Iraqi Freedom, the 2003 Iraq War. Utilizing uses and gratifications, hostile media perception, and cognitive dissonance perspectives as a basis, the researcher studied military spouses' media behaviors, perceived benefits of media usage, and whether hostile media perception and cognitive dissonance were present in this convenience sample of military spouses. Thirty military spouses participated in in-depth interviews. The results showed a desire for more positive news stories and less negative news stories about Operation Iraqi Freedom. Hostile media perception and cognitive dissonance responses were noted among participants–especially with regard to the media's tracking totals of soldier and civilian casualties. Military spouses in this sample found military news sources more credible than civilian news sources. They also described using news coverage for the purposes of gaining information, surveillance, political competency and empathy.
Keywords: Military spouses; News media; Iraq War; Uses and gratifications; Hostile media perception; Cognitive dissonance theory; Army; 2003; Journalism (0391); Mass Communications (0708)